Large-size high-toughness molybdenum-based composite material and preparation method thereof
Through powder metallurgy technology and cold isostatic pressing, high-temperature sintering and thermal deformation treatment, large-size high-strength tough molybdenum-based composite materials were prepared, which solved the problem of insufficient high-temperature strength and toughness of materials in the prior art, and realized the material's High performance and large size.
Patent Information
- Application Number
- CN202411558959.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
AI Technical Summary
It is difficult to prepare high-performance large-size molybdenum-based composite materials in the prior art, especially during the forging process, which is prone to defects such as cracking and stratification, resulting in insufficient high-temperature strength and toughness of the materials and cannot meet the use requirements in the aerospace field.
Preparation of molybdenum-based composite materials through powder metallurgy technology, the specific steps include: preparing molybdenum-based composite powder with mixed material, forming a pressing blank using cold isostatic pressing technology, and then undergoing high-temperature sintering and thermal deformation treatment, including forging deformation strengthening and annealing Heat treatment is performed to obtain large-size high-strength tough molybdenum-based composite materials.
The prepared large-size molybdenum-based composite materials have high room temperature and high temperature tensile strength, fracture toughness and flexural strength, and are resistant to ablation and impact, which can meet the use requirements in the aerospace field.
Smart Images

Figure CN119433269A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to a large-size high-strength and tough molybdenum-based composite material and a preparation method thereof. Background Art
[0002] Molybdenum and molybdenum alloys have been widely used in aerospace, nuclear industry, military industry and other fields due to their high melting point, high strength, ablation resistance and low linear expansion coefficient. In recent years, the requirements of aerospace equipment for long range and precision strike have been continuously improved, and large-size, high-strength and tough engine hot end component materials are urgently needed. Considering the long working time, high working temperature and harsh working environment of the engine, conventional molybdenum-based materials will have defects that are difficult to overcome in some service environments due to their low-temperature brittleness and poor high-temperature stability, which can easily cause serious engine ablation. In order to extend the life of molybdenum-based composites and overcome their intrinsic defects, some reinforcements are often added to pure molybdenum or its alloys to form molybdenum-based composite materials. Molybdenum-based composite materials not only have the excellent properties of the matrix itself, but also have some of the properties of the reinforcement, making them an ideal material for the preparation of high-temperature resistant and impact-resistant overload components of weapons and equipment. At present, the specifications of small-sized molybdenum-based composite materials developed in China are usually 12mm-40mm in diameter. Large-sized molybdenum-based composite materials need to be further improved due to problems such as forging and quality consistency. The core technical difficulty that causes this phenomenon is that the thermal conductivity of molybdenum-based composite materials is poor, and large-sized billets are prone to cracking during forging.
[0003] Patent CN112195385B discloses a method for preparing spherical CrCoNi medium entropy alloy reinforced molybdenum-based composite materials, which effectively promotes the densification and sintering of the material matrix and solves the problem of poor toughness of the molybdenum-based composite materials. However, the molybdenum-based composite materials prepared by this method are small in size and cannot meet the use requirements of large-size hot end materials for engine nozzles.
[0004] Patent CN1136047205B discloses a method for preparing a large-size deformation-resistant molybdenum alloy, which is prepared by powder metallurgy and is composed of the following weight percentages: W5%-15%, ZrO20.5%-2.5%, and the balance is Mo. The ceramic phase of the molybdenum alloy is only zirconium oxide, and the content is relatively small, which has limited effect on fine grain strengthening and dispersion strengthening, poor toughness, and poor high-temperature strength, and cannot meet the requirements for impact-resistant, high-strength and tough hot end materials for engine nozzles. Therefore, how to efficiently and conveniently prepare high-performance, large-size composite materials has become a challenge faced by the use of molybdenum-based composite materials. Summary of the invention
[0005] In view of the shortcomings and defects of the prior art, one of the objects of the present invention is to provide a method for preparing large-size and high-strength and tough molybdenum-based composite materials. The molybdenum-based composite materials prepared by this method have excellent properties such as high-temperature toughness, ablation resistance, and impact resistance. The diameter of the prepared molybdenum-based composite material rods can reach 65-80mm and the length can reach 2580mm, which can meet the use requirements in the aerospace field.
[0006] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0007] A method for preparing a large-size high-strength and high-toughness molybdenum-based composite material comprises the following steps:
[0008] The preparation steps of the molybdenum-based composite material powder are as follows: TiC, ZrO2 and high-purity Mo powder are weighed respectively according to weight percentage, and mixed to obtain the molybdenum-based composite material powder. The molybdenum-based composite material powder includes the following components by weight percentage: TiC: 1.5%-5.0%, ZrO2: 1.0%-3.0%, and the balance is high-purity Mo powder.
[0009] Isostatic pressing step: cold isostatic pressing the molybdenum-based composite material powder at a pressure of 200-230 MPa for 20-40 min, with a green density of 6.8-7.3 g / cm 3 .
[0010] High temperature sintering step: placing the compact into a medium frequency induction sintering furnace for high temperature sintering to obtain a molybdenum-based composite material sintered compact.
[0011] Thermal deformation step: subjecting the molybdenum-based composite material sintered blank to forging deformation strengthening and annealing heat treatment to obtain a large-sized high-strength and tough molybdenum-based composite material.
[0012] In the above-mentioned method for preparing large-size high-strength and tough molybdenum-based composite materials, as a preferred embodiment, in the preparation step of the molybdenum-based composite material powder, the Fisher particle size of ZrO2 is 1.0-1.5μm, the Fisher particle size of TiC is ≤5μm, and the Fisher particle size of high-purity molybdenum powder is 2.5-3.2μm.
[0013] In the above-mentioned method for preparing large-sized high-strength and tough molybdenum-based composite materials, as a preferred embodiment, in the static pressing step, the diameter of the pressed blank is 95-98 mm.
[0014] In the above-mentioned preparation method of large-size high-strength and tough molybdenum-based composite materials, as a preferred embodiment, the high-temperature sintering is set to staged temperature rising sintering, keeping warm at 1000°C for 30 minutes, keeping warm at 1400°C for 100 minutes, and keeping warm at 1930-1980°C for 270 minutes-360 minutes, so as to remove impurities.
[0015] The large-size high-strength and tough molybdenum-based composite material rod has a size of φ56-φ80 mm and a maximum length of 2580 mm. The room temperature tensile strength can reach up to 801 MPa and the fracture toughness can reach 30.2 MPa·m 1 / 2 The flexural strength reaches 1756MPa, and the high temperature strength at 800℃ can reach 450MPa.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects:
[0017] 1. The high-strength and tough molybdenum-based composite material designed and prepared by the present invention can be expanded to specifications of φ56-φ80mm, the longest length can reach 2580mm, the room temperature tensile strength can reach up to 801MPa, and the fracture toughness can reach 30.2MPa·m 1 / 2 The bending strength reaches 1756MPa, and the high temperature strength of 800℃ can reach 450MPa, which can meet the use requirements of ultra-long-range weapons and equipment.
[0018] 2. In this application, the addition of TiC and ZrO2 phases can enhance the high-temperature toughness and oxidation resistance of molybdenum-based composite materials. Doping a certain amount of TiC ceramic phase increases the density of the molybdenum matrix during the sintering process, while refining the grains, resulting in stress-induced phase transformation toughening. Part of the ZrO2 powder forms dispersed particles in the molybdenum matrix, thereby improving the toughness of the material. By adjusting the amount of TiC and ZrO2 powder added, the influence of the powder on the microstructure is obtained, and the high-temperature toughness, oxidation resistance, erosion resistance and mechanical strength of the molybdenum-based composite material are improved.
[0019] 3. The total forging deformation of the present invention is large, the forging passes are many, and the annealing process is added during the forging process to eliminate residual stress in time, thereby avoiding forging defects such as cracking and delamination of large-size molybdenum-based composite materials due to uneven heating inside and outside the rod during the forging process. The prepared large-size molybdenum-based composite materials have excellent high strength and toughness at room temperature and high temperature. The process is simple and suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of a large-sized, high-strength and tough molybdenum-based composite material powder prepared by the present invention;
[0021] Figure 2 A heat treatment process diagram of Example 3 provided by the present invention;
[0022] Figure 3 This is the EBSD image of the large-scale high-strength and tough molybdenum-based composite material obtained in Example 3 of the present invention;
[0023] Figure 4 This is a SEM image of the molybdenum-based composite material prepared in the present invention. DETAILED DESCRIPTION
[0024] The present invention is described below in conjunction with the accompanying drawings and specific embodiments. The embodiments described are only a part of the embodiments of the present invention, rather than all the embodiments.
[0025] Example 1
[0026] A large-size high-strength and tough molybdenum-based composite material is selected according to mass percentage, including 1.5% ZrO2 ceramic powder (Ferris grain size is 1.0-1.5μm), 2.5% TiC ceramic powder (Ferris grain size is ≤5μm), and the rest is high-purity Mo powder (Ferris grain size is 2.5-3.2μm).
[0027] The method for preparing the above-mentioned large-size high-strength and tough molybdenum-based composite material comprises the following steps:
[0028] Step 1: Mix the above powders using a V-type mixer for 36 hours, sieve twice with 80 mesh to obtain composite powder.
[0029] Step 2: The molybdenum-based composite material powder is cold isostatically pressed at a pressure of 200 MPa for 30 minutes, and the green density is 6.9 g / cm 3 , prepared into a compact with a diameter of 99 mm;
[0030] Step 3: Place the pressed green sheet into a medium frequency induction sintering furnace for high temperature sintering. The high temperature sintering temperature is 1930°C and the temperature is kept for 270 minutes. The high temperature sintering is set to staged temperature rise sintering. The diameter of the sintered green sheet is 89 mm.
[0031] Step 4: The sintered blank is subjected to forging deformation strengthening treatment, and a 1000t fast forging machine is used for rapid forging treatment. In the first forging pass, the heating temperature is 1600°C, the holding time is 60min, the final forging temperature is 1350°C, the pass deformation is 13%, and the forging speed is 90mm / s; in the second forging pass, the heating temperature is 1550°C, the holding time is 40min, the final forging temperature is 1400°C, the cumulative deformation of the pass is 30%, and the forging speed is 90mm / s. After the second pass, annealing treatment is carried out, the annealing temperature is 90℃, and the annealing time is 50min; in the third forging, the heating temperature is 1500℃, the holding time is 50min, the final forging temperature is 1350℃, the cumulative deformation of the pass is 49%, and the forging speed is 90mm / s; in the fourth forging, the heating temperature is 1450℃, the holding time is 60min, the final forging temperature is 1400℃, the cumulative deformation of the pass is 60%, and the forging speed is 100mm / s. After the fourth pass, annealing treatment is carried out again, the annealing temperature is 1150℃, and the annealing time is 70min.
[0032] The large-size high-strength and tough molybdenum-based composite material rod has a size of φ59 mm, a room temperature tensile strength of 771 MPa, and a fracture toughness of 26.9 MPa·m 1 / 2 , flexural strength is 1756MPa, and high temperature strength at 800℃ is 409MPa.
[0033] Embodiment 2:
[0034] A large-size high-strength and tough molybdenum-based composite material is selected according to mass percentage, including 2.5% ZrO2 ceramic powder (Fisherman particle size is 1.0-1.5μm), 2% TiC ceramic powder (Fisherman particle size is ≤5μm), and the rest is high-purity Mo powder (Fisherman particle size is 2.5-3.2μm).
[0035] The method for preparing the above-mentioned large-size high-strength and tough molybdenum-based composite material comprises the following steps:
[0036] Step 1: Mix the above powders using a V-type mixer for 40 hours, sieve twice with 80 mesh to obtain composite powder.
[0037] Step 2: The molybdenum-based composite material powder is subjected to cold isostatic pressing at a pressure of 210 MPa for 20 minutes, and the green density is 6.8 g / cm 3 , prepared into a compact with a diameter of 121 mm.
[0038] Step 3: Place the pressed green sheet into a medium frequency induction sintering furnace for high temperature sintering. The high temperature sintering temperature is 1950° C. and the temperature is kept for 330 minutes. The high temperature sintering is set to staged temperature rise sintering. The diameter of the sintered green sheet is 107 mm.
[0039] Step 4: The sintered blank is subjected to forging deformation strengthening treatment, and a 1000t fast forging machine is used for rapid forging treatment. In the first forging pass, the heating temperature is 1600°C, the holding time is 65min, the final forging temperature is 1400°C, the pass deformation is 17%, and the forging speed is 100mm / s; in the second forging pass, the heating temperature is 1500°C, the holding time is 45min, the final forging temperature is 1370°C, the cumulative deformation of the pass is 35%, and the forging speed is 105mm / s. After the second pass, annealing treatment is carried out, the annealing temperature is 1000℃, and the annealing time is 40min; in the third forging, the heating temperature is 1470℃, the holding time is 45min, the final forging temperature is 1370℃, the cumulative deformation of the pass is 51%, and the forging speed is 100mm / s; in the fourth forging, the heating temperature is 1470℃, the holding time is 65min, the final forging temperature is 1370℃, the cumulative deformation of the pass is 65%, and the forging speed is 100mm / s. After the fourth pass, annealing treatment is carried out again, the annealing temperature is 1150℃, and the annealing time is 60min.
[0040] The large-size high-strength and tough molybdenum-based composite material rod has a size of φ71 mm, a room temperature tensile strength of 790 MPa, and a fracture toughness of 27.4 MPa·m 1 / 2 , flexural strength 1750MPa, 800℃ high temperature strength 415MPa.
[0041] Embodiment 3:
[0042] A large-size high-strength and tough molybdenum-based composite material is selected according to mass percentage, including 3.5% ZrO2 ceramic powder (Fisherman particle size is 1.0-1.5μm), 1.5% TiC ceramic powder (Fisherman particle size is ≤5μm), and the rest is high-purity Mo powder (Fisherman particle size is 2.5-3.2μm).
[0043] The method for preparing the above-mentioned large-size high-strength and tough molybdenum-based composite material comprises the following steps:
[0044] Step 1: Mix the above powders using a V-type mixer for 48 hours, sieve twice through 80 mesh to obtain composite powder.
[0045] Step 2: The molybdenum-based composite material powder is cold isostatically pressed at a pressure of 230 MPa for 40 minutes, and the green density is 7.2 g / cm 3 , prepared into a compact with a diameter of 149 mm;
[0046] Step 3: Place the pressed green sheet into a medium frequency induction sintering furnace for high temperature sintering. The high temperature sintering temperature is 1970°C and the temperature is kept for 360 minutes. The high temperature sintering is set to staged temperature rise sintering. The diameter of the sintered green sheet is 134 mm.
[0047] Step 4: The sintered blank is subjected to forging deformation strengthening treatment, and a 1000t fast forging machine is used for rapid forging treatment. In the first forging pass, the heating temperature is 1550°C, the final forging temperature is 1400°C, the holding time is 70min, the pass deformation is 20%, and the forging speed is 110mm / s; in the second forging pass, the heating temperature is 1550°C, the final forging temperature is 1380°C, the holding time is 50min, the cumulative deformation of the pass is 37%, and the forging speed is 110mm / s. After the second pass, annealing treatment is carried out, the annealing temperature is 1100℃, and the annealing time is 30min; in the third forging, the heating temperature is 1500℃, the holding time is 50min, the final forging temperature is 1350℃, the cumulative deformation of the pass is 53%, and the forging speed is 110mm / s; in the fourth forging, the heating temperature is 1450℃, the final forging temperature is 1350℃, the holding time is 60min, the cumulative deformation of the pass is 58%, and the forging speed is 90mm / s. After the fourth pass, annealing treatment is carried out again, the annealing temperature is 1200℃, and the annealing time is 35min.
[0048] The large-size high-strength and tough molybdenum-based composite material rod has a size of φ80 mm, a length of 2580 mm, a room temperature tensile strength of 801 MPa, and a fracture toughness of 30.2 MPa·m 1 / 2 , flexural strength is 1756MPa, and high temperature strength at 800℃ is 450MPa.
Claims
1. A method for preparing a large-size high-strength and tough molybdenum-based composite material, characterized in that: The steps include: Preparation of molybdenum-based composite material powder: select TiC: 1.5%-5.0%, ZrO2: 1.0%-3.0% according to weight percentage, and the balance is Mo, use a mixer to mix the powder for 36-48 hours, sieve through 80 mesh twice, and prepare the molybdenum-based composite material powder for vacuum packaging; Static pressing: cold isostatic pressing is performed on the molybdenum-based composite material powder to form a pressed green sheet at a pressure of 200-230 MPa and the pressure is maintained for 20-40 minutes; High temperature sintering: placing the pressed green sheet into a medium frequency induction sintering furnace for high temperature sintering to obtain a molybdenum-based composite material sintered green sheet; the high temperature sintering temperature is 1930-1980° C., and the heat preservation time is 270 min-360 min; Thermal deformation: The molybdenum-based composite material sintered blank is subjected to forging deformation strengthening treatment to obtain large-size forged bars; a fast forging machine is used for rapid forging treatment, the initial forging temperature is 1450℃-1600℃, the final forging temperature is controlled at 1350℃-1400℃, the total forging deformation is controlled at 58%-65%, and a total of four forging passes are performed. Each forging pass requires heating, heat preservation and forging, and annealing treatment is added every two passes; among them, In the first forging, the heating temperature is 1550℃-1600℃, the holding time is 60min-70min, the final forging temperature is controlled at 1350℃-1400℃, the pass deformation is 13%-20%, and the forging speed is 90-110mm / s; In the second forging, the heating temperature is 1500℃-1550℃, the holding time is 40min-50min, the final forging temperature is controlled at 1350℃-1400℃, the cumulative deformation of the pass is 30%-37%, the forging speed is 90-110mm / s, the annealing temperature is 900℃-1100℃, and the annealing time is 30-50min; In the third forging, the heating temperature is 1450℃-1500℃, the holding time is 40min-50min, the final forging temperature is controlled at 1350℃-1400℃, the cumulative deformation of the pass is 49%-53%, and the forging speed is 90-110mm / s; In the fourth forging pass, the heating temperature is 1450℃-1500℃, the holding time is 60min-70min, the final forging temperature is controlled at 1350℃-1400℃, the cumulative deformation of the pass is 58%-65%, the forging speed is 90-110mm / s, the annealing temperature is 1100℃-1200℃, and the annealing time is 60-90min.
2. The method for preparing a large-size high-strength and tough molybdenum-based composite material according to claim 1, characterized in that: In the step of preparing the molybdenum-based composite material powder, the Fisher grain size of the ZrO2 is 1.0-1.5 μm, the Fisher grain size of the TiC is ≤5 μm, and the Fisher grain size of the high-purity molybdenum powder Mo is 2.3-3.8 μm.
3. The method for preparing a large-size high-strength and tough molybdenum-based composite material according to claim 1, characterized in that: In the static pressing step, the diameter of the green compact is 99-151 mm, and the density of the green compact is controlled at 6.8-7.3 g / cm 3 .
4. The method for preparing a large-size high-strength and tough molybdenum-based composite material according to claim 1, characterized in that: The high temperature sintering is set to be staged temperature rising sintering, keeping warm at 1000° C. for 30 minutes, keeping warm at 1400° C. for 100 minutes, and keeping warm at 1930-1980° C. for 270 minutes-360 minutes, so as to remove impurities.
5. The method for preparing a large-size high-strength and tough molybdenum-based composite material according to claim 4, characterized in that: In the high temperature step, the diameter of the molybdenum-based composite material sintered blank is 88-135 mm.
6. The method for preparing a large-size high-strength and tough molybdenum-based composite material according to claim 1, characterized in that: A 1000t fast forging machine is used for forging deformation strengthening process.
7. The method for preparing a large-size high-strength and tough molybdenum-based composite material according to claim 1, characterized in that: In the rapid forging step, the diameter of the molybdenum-based composite material forging rod is 56-80 mm.
8. A large-size, high-strength and tough molybdenum-based composite material, characterized in that: It is prepared by the method according to any one of claims 1 to 7, wherein the large-size high-strength and tough molybdenum-based composite material rod has a size of The maximum length can reach 2580mm, the room temperature tensile strength can reach up to 801MPa, and the fracture toughness can reach 30.2MPa·m 1 / 2 The flexural strength reaches 1756MPa, and the high temperature strength at 800℃ can reach 450MPa.
Citation Information
Patent Citations
A high-temperature resistant, high-strength, and high-toughness molybdenum-based composite material and its preparation method
CN112195385B